Reciclagem de borra oleosa: uma contribuição para a gestão sustentável dos resíduos da indústria de petróleo em Sergipe - Alves, Mara Régia Falcão Viana (2003)
The oil industry in Sergipe State has reproduced the ongoing development model based on the use of fossil fuels as the main source of energy, and has generated some pollutants which are hard to treat or dispose of, called oil sludge, basically consisting of oil, solids and water. The final disposition, treatment and recycling of this waste is considered a high priority of the oil companies in the discussion of the policies related to its sustainable management. To decrease the environmental impacts resulting from the final disposition of the pollutant, the objective of this work was to study an alternative of recycling the oil sludge as one component in the mixture of ceramic blocks producing for the civil construction industry. Additionally, we tried to define environmental indicators as a very important tool related to oil residues management policies. A characterization of the oil sludge was carried out to define the best treatment related to the addition of the residue mixtures with clay and water to make the ceramic blocks in rates ranging from 0 to 25% in weight. The quality of the ceramic blocks was evaluated based on mechanical resistance, water absorption, efflorescence, soluble salts content and retention capacity of heavy metals, which are measured by leaching and solubilization tests. A better mixture was achieved with the addition of oil sludge until the rate of 20% to make the ceramic blocks, with maintenance of the desirable characteristics related to this type of construction supply, besides no negative effects to the environment. Oil sludge recycling may contribute to the improvement of the eco-efficiency of the ceramic industry, reducing the pressure toward the use of natural resources, and also providing a sustainable use of this hard to manage pollutant to the oil industry. Fifteen environmental indicators were proposed to help evaluate the impacts of the actions and policies to analyze or adopt new solutions to solve environmental problems, and to identify the competencies and responsibilities of decision makers.